2018
DOI: 10.1111/bcpt.13161
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with tenofovir alafenamide fumarate worsens the lipid profile of HIV‐infected patients versus treatment with tenofovir disoproxil fumarate, each coformulated with elvitegravir, cobicistat, and emtricitabine

Abstract: Two elvitegravir/cobicistat-based therapies combined with emtricitabine/tenofovir disoproxil fumarate (EVG/c/FTC/TDF) or emtricitabine/tenofovir alafenamide fumarate (EVG/c/FTC/TAF) are currently available for HIV patients. This study evaluated the modifications in the lipid profile of patients who received these treatments in the last three years at our institution. A retrospective observational study in HIV-infected patients who received EVG/c/FTC/TDF or EVG/c/FTC/ TAF from January 2015 to January 2018 at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 26 publications
9
36
0
Order By: Relevance
“…We found that after switching from TDF to TAF the prevalence of patients with LDL above their CV target increased significantly; as a consequence, clinicians prescribed lifestyle intervention and in some cases lipid‐lowering drugs in order to intervene to modify CV risk factors. The presence of cobicistat in the cART regimen was independently associated with a 2.5‐fold increase in the risk of LDL above the CV target, as compared with cobicistat‐free regimens, confirming literature data on the metabolic impact of boosted cART regimens [12].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…We found that after switching from TDF to TAF the prevalence of patients with LDL above their CV target increased significantly; as a consequence, clinicians prescribed lifestyle intervention and in some cases lipid‐lowering drugs in order to intervene to modify CV risk factors. The presence of cobicistat in the cART regimen was independently associated with a 2.5‐fold increase in the risk of LDL above the CV target, as compared with cobicistat‐free regimens, confirming literature data on the metabolic impact of boosted cART regimens [12].…”
Section: Discussionsupporting
confidence: 76%
“…Indeed, Cid‐Silva P et al . [12], comparing the lipid parameters in patients starting E/C/F/TAF vs . E/C/F/TDF, showed that patients on TAF had higher increase in lipids at 48 weeks that resulted in an increased probability of lipid levels above the normal range.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are still few data about the real life effects of switching from TDF to TAF, especially in the context of dyslipidemia. In a retrospective observational study of 384 patients who received elvitegravir/cobicistat/FTC/TDF (151 patients) or elvitegravir/cobicistat/FTC/TAF (233 patients), a significant increase in TC and LDL in naïve patients, and in TC, LDL, HDL, TC/HDL, LDL/HDL and TG in experienced patients, were observed after 48 weeks of TAF, while all lipids levels remained stable in the TDF arm [12]. In addition, the number of lipid-lowering drugs prescribed to patients who received TAF (11.9%) was almost triple compared to TDF (4,7%) [12].…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective observational study of 384 patients who received elvitegravir/cobicistat/FTC/TDF (151 patients) or elvitegravir/cobicistat/FTC/TAF (233 patients), a significant increase in TC and LDL in naïve patients, and in TC, LDL, HDL, TC/HDL, LDL/HDL and TG in experienced patients, were observed after 48 weeks of TAF, while all lipids levels remained stable in the TDF arm [12]. In addition, the number of lipid-lowering drugs prescribed to patients who received TAF (11.9%) was almost triple compared to TDF (4,7%) [12]. The aim of this observational retrospective study was to evaluate the impact on lipids of switching from RPV/FTC/TDF to RPV/FTC/TAF single tablet regimen in a real life context and to investigate if the effects on lipids were different in people with different baseline values of TC and TG.…”
Section: Introductionmentioning
confidence: 99%
“…Combined ARTs (cARTs) are highly effective in the virological suppression of HIV infection 3 . In addition to two nucleoside analog reverse transcriptase inhibitors (NRTIs), the combined use of a third active drug is recommended, namely an integrase strand transfer inhibitor (INSTI), a non-nucleoside reverse transcriptase inhibitor (NNRTI), or an amplified protease inhibitor (PI) for the treatment of HIV-infected persons 4 . HIV-positive patients are at risk of both acute kidney injury (AKI) and chronic kidney disease (CKD) due to drug nephrotoxicity, HIV-associated nephropathy (HIVAN), and immune complex kidney diseases (HIVICK) 5 .…”
Section: Introductionmentioning
confidence: 99%